2020
DOI: 10.1128/jvi.00800-20
|View full text |Cite
|
Sign up to set email alerts
|

Exocytosis of Progeny Infectious Varicella-Zoster Virus Particles via a Mannose-6-Phosphate Receptor Pathway without Xenophagy following Secondary Envelopment

Abstract: The literature on egress of different herpesviruses after secondary envelopment is contradictory. In this report, we investigated varicella-zoster virus (VZV) egress in a cell line from a child with Pompe Disease, a glycogen storage disease caused by a defect in the enzyme required for glycogen digestion. In Pompe cells, both the late autophagy pathway and the mannose-6-phosphate receptor (M6PR) pathway are interrupted. We have postulated that intact autophagic flux was required for higher recoveries of VZV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 79 publications
(123 reference statements)
0
15
0
Order By: Relevance
“…Comparisons of healthy and autophagy-defective cells also indicated the existence of two distinct egress pathways for VZV. Transmission EM analysis showed that in healthy cells, viral capsids seem to accumulate in large vacuoles containing a high number of particles, whereas in the autophagy-defective cells, only small vacuoles, containing a single viral particle each, appear [52]. Importantly, no signs of xenophagy were observed in either the healthy or the deficient cells.…”
Section: Divergent Roles Of Autophagic Vacuoles Leading To Either Vzv Egress or Viral Degradationmentioning
confidence: 97%
See 2 more Smart Citations
“…Comparisons of healthy and autophagy-defective cells also indicated the existence of two distinct egress pathways for VZV. Transmission EM analysis showed that in healthy cells, viral capsids seem to accumulate in large vacuoles containing a high number of particles, whereas in the autophagy-defective cells, only small vacuoles, containing a single viral particle each, appear [52]. Importantly, no signs of xenophagy were observed in either the healthy or the deficient cells.…”
Section: Divergent Roles Of Autophagic Vacuoles Leading To Either Vzv Egress or Viral Degradationmentioning
confidence: 97%
“…However, in view of the strong cell-type dependency that has been observed in the context of autophagy, further studies in various different cell or organ cultures are required to better understand this process in greater detail. To date, upregulated autophagy following VZV infection has been described in fibroblasts, mainly MRC-5, but also in primary cells, MeWo cells and keratinocytes [44,52,55]. Furthermore, HeLa cells transfected with VZV glycoproteins presented with an enlarged ER and increased LC3-punctae formation [45].…”
Section: Activation Of Autophagy Flux During Vzv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, VZV utilizes an amalgam of endosomal and autophagosomal pathways to perform exocytosis of complete viral particles, as observed by electron microscopy, which shows virions in single-membraned vesicles carrying both Rab11 and LC3, which resembled amphisomes [ 209 ]. Alternatively, VZV has been shown to have the ability to bind to the mannose-6-phosphate receptor in late endosomes as a mechanism to egress from infected melanoma cells or fibroblasts, regardless of the autophagosome pathway [ 210 ]. A recent report indicates that the VZV glycoprotein M (gM) contains two tyrosine-XX-bulk hydrophobic amino acid domains and one dileucine trafficking-domain associated with trans-Golgi sorting vesicles, which implies that gM is targeted to endosomal-lysosomal compartments to help viral maturation [ 211 ].…”
Section: Exocytosis Vesicles Hijacked By Herpesvirusesmentioning
confidence: 99%
“…The γ1AP-1/μ1B also binds, like γ1AP-1/μ1A, to the TGN and it even can substitute γ1AP-1/μ1A in MPR sorting [ 32 ]. Due to these ubiquitous house-keeping functions of MPR300-mediated protein sorting, it is not surprising that several viruses, like HIV-1, VZV, and rotaviruses, bind MPR300 for cell entry via CME, as well as for cell egress [ 33 , 34 , 35 , 36 , 37 ]. Another excellent example of exploiting the specificity of AP-1 are HCV and herpesviruses that skillfully select adaptins to avoid apical surfaces and avoid host immune response.…”
Section: Main Bodymentioning
confidence: 99%